2010
DOI: 10.1071/rdv22n1ab1
|View full text |Cite
|
Sign up to set email alerts
|

1 Progesterone as the Driving Regulatory Force Behind Serum FSH Concentrations and Antral Follicular Growth in Cyclic Ewes

Abstract: Ovarian antral follicles in sheep grow in an orderly succession, producing typically 3 to 4 follicular waves per 17-day estrous cycle. Each wave is preceded by a transient increase in circulating FSH concentrations. The mechanism controlling the number of recurrent FSH peaks and emerging follicular waves remains unknown. During the ewe's estrous cycle, the time between the first 2 FSH peaks and days of wave emergence is longer than the intervals separating the ensuing FSH peaks and follicular waves. The prolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…7). This is most likely due to alterations in intermediate FSH metabolism induced by a rapid change in steroid milieu [75,76]. Lower serum levels of P 4 or synthetic progestin tend to increase the less acidic isoforms of FSH in circulation causing FSH to be cleared from the blood at a faster rate [77].…”
Section: Endogenous and Exogenous Fsh Concentrationsmentioning
confidence: 99%
“…7). This is most likely due to alterations in intermediate FSH metabolism induced by a rapid change in steroid milieu [75,76]. Lower serum levels of P 4 or synthetic progestin tend to increase the less acidic isoforms of FSH in circulation causing FSH to be cleared from the blood at a faster rate [77].…”
Section: Endogenous and Exogenous Fsh Concentrationsmentioning
confidence: 99%
“…Many members of the TGFβ family are considered important intraovarian growth factors (Shimasaki et al, 2004). The FecB mutation affects the inhibitory function of the BMP4/GDF5 ligands by inhibiting the activity of BMPR-IB and increasing progesterone levels (Ruoss et al, 2009), which appears to be a key endocrine signal that controls the cyclical increase in ovine serum FSH concentration and the number of follicular waves (Baby & Bartlewski, 2011). Early research has shown that interference with BMPRIB expression inhibits estradiol production while inducing apoptosis in granulosa cells F I G U R E 9 Changes in mRNA and protein expression in the different genotypes (FecB).…”
Section: Ovarymentioning
confidence: 99%